Density‐dependent offspring interactions do not explain macroevolutionary scaling of adult size and offspring size. (12th September 2019) - Rollinson, Njal; Nilsson‐Örtman, Viktor; Rowe, Locke
Abstract: Most life forms exhibit a correlated evolution of adult size (AS) and size at independence (SI), giving rise to AS–SI scaling relationships. Theory suggests that scaling arises because relatively large adults have relatively high reproductive output, resulting in strong density‐dependent competition in early life, where large size at independence provides a competitive advantage to juveniles. The primary goal of our study is to test this density hypothesis, using large datasets that span the vertebrate tree of life (fishes, amphibians, reptiles, birds, and mammals). Our secondary goal is to motivate new hypotheses for AS–SI scaling by exploring how subtle variation in life‐histories among closely related species is associated with variation in scaling. Our phylogenetically informed comparisons do not support the density hypothesis. Instead, exploration of AS–SI scaling among life‐history variants suggests that steeper AS–SI scaling slopes are associated with evolutionary increases in size at independence. We suggest that a positive association between size at independence and juvenile growth rate may represent an important mechanism underlying AS–SI scaling, a mechanism that has been underappreciated by theorists. If faster juvenile growth is a consequence of evolutionary increases in size at independence, this may help offset the cost of delayed maturation, leading to steeper AS–SI scaling slopes.